2017
DOI: 10.14744/ejmo.2017.43531
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prognostic factors in epithelial ovarian cancer

Abstract: O varian cancers constitute 4% of female cancers. Ovarian cancer is the second most common gynecological cancer.[1] About 95% of the ovarian malignancies are epithelial tumors. Serous ovarian cancer is the most common epithelial ovarian cancers. Its treatment modalities include surgery, adjuvant chemotherapy, and supportive therapy. It has a rather poor course of prognosis. 5-year survival rate of ovarian cancer is about 40-45%. This ratio ranges from 15% to 95% based on various factors affecting prognosis. [2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This result is consistent with previous reports analyzing prognosis of elderly patients with advanced OvCa 5,20 . There are some studies that linked aging and tumor progression.…”
Section: Discussionsupporting
confidence: 94%
“…This result is consistent with previous reports analyzing prognosis of elderly patients with advanced OvCa 5,20 . There are some studies that linked aging and tumor progression.…”
Section: Discussionsupporting
confidence: 94%
“…Onal et al 11 found that patients with metastasis at the time of diagnosis and ascites before surgery had a statistically significant higher rate of recurrence. Similarly, patients with stage IV are more likely to relapse than those with stage III.…”
Section: Discussionmentioning
confidence: 99%
“…In present research the p value for BMI when compared among normal and non-normal categories was 0.89 2 . While in another study which was carried out on 119 women of stage III and IV diagnosed with ovarian cancer, when BMI was compared it was non significant p 0.263 19,20 . Another study presented survival prognosis in early stage (90%) and 53.3% late stage 15,21 , which is in agreement with present study with 72% stage I, II vs 43% stage III, IV.…”
Section: Discussionmentioning
confidence: 91%